Plant Cultivation and Indian Knowledge System: An Exploration of the Available Scholarly Literature (Annals of Library and Information Studies, 2025)
The interest in the traditional practices of plant cultivation has gained momentum in India in the past few decades. We are witnessing a revival of ancient concepts, such as Vrikshayurveda. The underlying reasons of this resurgence could be attributed to the modern unsustainable cultivation practices resulting in the increasingly depleting soil quality of the farmlands, low nutritional value of the produce, indiscriminate exploitation of the forest resources, water pollution caused by chemical fertilisers and pesticides, and the consequent diseases posed to human and animal life, to name a few. Needless to say, all these disturbing issues pose a high threat to not only our food security but also to our very existence on this planet. Meanwhile, India is poised to be a completely developed nation by 2047 as envisioned by the sentiment of Viksit Bharat@2047. Clearly, to enable Bharat to be completely developed by that time, appropriate ground-breaking interventions need to be undertaken from today itself to mitigate the existing problems. The scientific community in India is now actively looking for solutions to these problems in the Indian Knowledge System (IKS). Lately there has been an impetus in the research carried out by universities and institutions on the feasibility of plant cultivation that is based on the IKS. The Government of India has also been supportive in this regard with several Ministries, such as the Ministry of AYUSH and Ministry of Agriculture paying special attention to the development of innovative solutions towards sustainable plant cultivation practices. In this regard, a considerable amount of work has been done by researchers and scientists in mining the knowledge available in the IKS and practicing them. However, it is felt that the information available to us regarding IKS for plant cultivation is still growing and there is a considerable scope for continued research on exploring IKS, especially that available in regional languages. This study is exploratory research on the available literature on plant cultivation practices and the IKS. This paper attempts not only to explain the various types of plant cultivation practices as mentioned in the IKS but also to highlight the available literature on the modern scientific experiments and innovations that provide the evidence of the efficacy of the IKS-based plant cultivation techniques. The collated and updated literature presented in this paper is expected to assist the researchers and policy makers to take an informed decision on the adoption of best practices in plant cultivation using IKS. The study is also expected to provide insight into the design, development and offering of customised referral services in IKS-based resources on plant cultivation by the libraries.